PEMBELAJARAN MENABUH GAMELAN ANGKLUNG DI BANJAR JEMPINIS DESA ADAT PERERENAN, KECAMATAN MENGWI, KABUPATEN BADUNG - I Nyoman Winyana, Winyana; I Nyoman Surianta, Surianta; Ni Luh Putu Trisdyani Trisdyani; I Gusti Agung Ngurah Harry Chandra Diva Diva (WIDYANATYA, 2023)
ABSTRACT Art is a complex of elements that is very popular with residents, so it seems as if it dominates Balinese life. The art of karawitan is an important part of Balinese life that has been inherited since ancient times. There are two types of Angklung gamelan in the Pererenan area, namely in Banjar Jempinis and in Banjar Pengembungan. Banjar Jempinis is part of Pererenan Village which is located in Mengwi District. The problems and objectives of this study are; to find out about learning to play the angklung gamelan. To understand the process of learning to play the angklung gamelan. To find out the implications in learning to play the angklung gamelan. The method approach used is a qualitative method because there is more primary and secondary data in the field. Data was collected using observation techniques, interviews and completed using a triangulation approach before being concluded as research results. An analytical approach using learning theory and functional theory in analyzing the problem. The findings of this research show that apart from the learning methods generally used, conventional learning methods are also used in learning gemelan angklung in Banjar Jempinis Mengwi. Found that there are educational values ??that are applied which are related to scientific learning of art, social values, religious values ??and also character. Keywords: Learning, Gamelan Angklung, Banjar Jempinis.